PENCIPTAAN ULANG MANUSIA: IMPLIKASI TEOLOGI KRISTEN DALAM ERA POSTHUMANIS - Evriyani Lambang Mandi’; Dorce Du’pa; Sita Pasangkin (ADISAM PUBLISHER, 2023)
This study discusses the implications of Christian theology on the concept of human re-creation in the context of the posthuman era. The research is based on a qualitative approach through the analysis of literature that explores classic Christian theological texts as well as contemporary works discussing posthumanism. The aim is to understand how the Christian perspective on modified or enhanced humans interacts with the posthumanist paradigm that increasingly dominates the developments in technology and science today. Through in-depth analysis of theological works, this research identifies that Christian theology faces significant challenges in integrating the concept of posthumanism. While there are potential elements in Christian teachings that can support the idea of human re-creation, there are also points of tension between the Christian view of human dignity and the posthumanist vision of technological progress. This study yields a deeper understanding of the points of convergence and conflict between Christian theology and posthumanism, and provides insights into how Christian teachings can respond to the ethical and moral challenges arising from technological advancements. Through this research, conclusions are drawn that make a significant contribution in exploring the complex interaction between posthumanism and Christian theology, and provide a foundation for further discussion on the role and responsibilities of humans in the evolving posthuman era